Electric and Thermoelectric Properties of LaFeO3 Compounds Doped by Ti, Co and Cu ions - Minh, Dang Le; Hoa, Vu Nu Mai; Dinh, Nguyen Ngoc; Thuy, Nguyen Thi (VNU Journal of Science: Mathematics - Physics; Vol 29 No 3, 2013)
Abstract: LaFeO 3 doped Ti, Co and Cu with the high thermoelectric property has been prepared by solid state reaction method at high temperature. The phase composition, crystalline structure have been determined by XRD. Study on the electric (ρ-T), (σ-T), thermoelectric properties such as the Seebeck coefficient (S), power factor (PF) has been performed. The doping of ions Co and Cu increased the electric conductivity (σ) and power factor (PF) of the samples.